News as program content on FM radio a descriptive study - Devierte, Ma. Avegail Opiña 1980- (College of Mass Communication, University of the Philippines, 2014)
"FM radio has always been synonymous with music. Yet, there is more to FM radio than the free music it provides. This thesis then explores the often-sidestepped program content of FM radio: the news. Anchored on McQuail's news production, this thesis answered the research problem: How does FM radio produce news as program content? As FM radio reflects what McQuail said about the internal structure of media workforce shaping the work of a media organization, this study determined the hierarchy of Fm radio personnel who routinize news production to be able to incorporate it in the programming of their music format. Affirming McQuail's news production's two-step process of selecting and processing, three interviews from different music formats said that the top of the hierarchy - the bosses - selects which news items to air and the bottom of the hierarchy - the on-air personalities - processes them with their style of news reading. Regardless of format, producing news for Fm radio has the dual mission of informing the listeners as well as entertaining them. This thesis was also guided by the uses and gratification's theory to address the effects of how FM radio produces news and how, in general, FM radio satisfies different social and psychological needs. The so-called effects were gauged by how the 10 focus group discussion participants and 340 survey respondents from all over Metro Manila revealed FM radio in terms of being used for diversion, companion, identity reinforcement, and source of information. As a mass medium, FM radio may have taken-for-granted role of providing free music. This study, however, has proven that, much like its musical content, FM radio's "talk" content is also a part of its programming for which listeners also tune in. Hence, when news is a regular part of the program, FM radio listeners recognize this and acknowledge the information they get."